A Comparative Analysis of Reading Self-Efficacy of Turkology Students - Önder Çangal; Umut Başar (Foxton Books, 2021)
The Turkology Departments in countries other than Turkey fulfill two functions. First, they aim to equip their students with sufficient Turkish language proficiency. Second, they offer students a university degree from the Language, History and Literature program. Therefore, regarding the students who are studying in these departments, their competence in Turkish language skills on an academic level is significant. Thus, the aim of this study is to determine the reading skills self-efficacy of Turkology students studying in Bosnia and Herzegovina and Algeria. The study explored if the students' reading self-accicay changed in line with any of the variables of country origin, gender, and student achievement level. The research data were collected by adopting the "Reading self-efficacy scale of those who learn Turkish as a foreign language" prepared by Güngör and Kan (2020), and the data obtained was analyzed using IBM SPSS Statistics 25.0 package program. According to the results of the study, it was seen that the reading self-efficacy of Bosnia and Herzegovinian students was higher than the Algerians. Additionally, it was found out that as the achievement scores and language proficiency levels of the students increased their reading self-efficacy scores also increased. Next, the self-efficacy scores of the graduate students were found to be higher than those of the undergraduate students. In addition, there was no significant difference between the self-efficacy level of the students participating in the study according to their gender. Finally, based on the findings, suggestions were given to increase the reading self-efficacy of the students at the end of the study.